2012
DOI: 10.1002/bit.24425
|View full text |Cite
|
Sign up to set email alerts
|

Closed system isolation and scalable expansion of human placental mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSC) are emerging as a leading cellular therapy for a number of diseases. However, for such treatments to become available as a routine therapeutic option, efficient and cost-effective means for industrial manufacture of MSC are required. At present, clinical grade MSC are manufactured through a process of manual cell culture in specialized cGMP facilities. This process is open, extremely labor intensive, costly, and impractical for anything more than a small number of patients. While i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 56 publications
4
85
0
1
Order By: Relevance
“…Induction medium was exchanged twice per week over the culture period. Following 14 days of induction, cultures were characterized for either bone-like matrix (osteogenesis) or lipid vacuoles (adipogenesis) as per our previous publication In previous publications, we have characterized the differentiation potential of placental-derived MSC more extensively 4,5 . Placental-derived MSC osteogenesis is similar to bone marrow-derived MSC, while adipogenesis is generally less efficient in placental-derived MSC 5 .…”
Section: Characterization Of Placental Msc In Vitromentioning
confidence: 99%
See 4 more Smart Citations
“…Induction medium was exchanged twice per week over the culture period. Following 14 days of induction, cultures were characterized for either bone-like matrix (osteogenesis) or lipid vacuoles (adipogenesis) as per our previous publication In previous publications, we have characterized the differentiation potential of placental-derived MSC more extensively 4,5 . Placental-derived MSC osteogenesis is similar to bone marrow-derived MSC, while adipogenesis is generally less efficient in placental-derived MSC 5 .…”
Section: Characterization Of Placental Msc In Vitromentioning
confidence: 99%
“…MSC derived from placenta have long-term proliferation 5 and immunomodulatory capacity 6 , superior to bone marrow-derived MSC. In a previous study, we demonstrated that a single term placenta contained sufficient MSC for the manufacture of up to 7,000 clinical doses 4 . These characteristics make placenta an ideal source tissue for the manufacture of allogeneic MSC.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations